Detection and analysis of autophagy in the American alligator (Alligator mississippiensis). Issue 3 (15th February 2020) - Hale, Amber; Merchant, Mark; White, Mary
Abstract: In response to environmental temperature depression in the fall and winter, American alligators ( Alligator mississippiensis ) brumate. Brumation is characterized by lethargy, fasting, decreased metabolism, and decreased body temperature. During brumation, alligators will periodically emerge for basking or other encounters when environmental conditions permit. This sporadic activity and lack of nutrient intake may place strain on nutrient reserves. Nutrient scarcity, at the cellular and/or organismal level, promotes autophagy, a well‐conserved subcellular catabolic process used to maintain energy homeostasis during periods of metabolic or hypoxic stress. An analysis of the putative alligator autophagy‐related proteins has been conducted, and the results will be used to investigate the physiological role of autophagy during the brumation period. Using published genomic data, we have determined that autophagy is highly conserved, and alligator amino acid sequences exhibit a high percentage of identity with human homologs. Transcriptome analysis conducted using liver tissue derived from alligators confirmed the expression of one or more isoforms of each of the 34 autophagy initiation and elongation genes assayed. Five autophagy‐related proteins (ATG5, ATG9A, BECN1, ATG16L1, and MAP1‐LC3B), with functions spanning the major stages of autophagy, have been detected in alligator liver tissue by western blot analysis. In addition, ATG5 was detected in alligator liver tissue by immunohistochemistry. This is the first characterization of autophagy in crocodylians, and the first description of autophagy‐related protein expression in whole blood. Abstract : Expression analysis and homology comparison of the American alligator and human canonical autophagy genes to inform protein detection and future studies. Research Highlights: Autophagy pathway protein sequences, functional domains, and regulation points are highly conserved between crocodylians and humans. ATG5 was detected in whole blood from crocodylians, allowing for the use of less invasive longitudinal sampling.